2006
DOI: 10.1002/jor.20205
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of surface modifications of extrasynovial tendon to improve its gliding ability in a canine model in vitro

Abstract: Previous studies have shown that the carboxyl groups in hyaluronic acid (HA) could be activated by 1-ethy 1-3-[3-dimethylaminopropyl] carbodiimide hydrochloride (EDC)/N-hydroxysuccinimide (NHS) to form intermediate O-acylisoureas, which can chemically bind to exposed amino groups on the tendon surface, leading to improved gliding ability. However, the optimal ratio and concentrations of the components in this chemical mixture were not investigated. The purpose of this study was to optimize the constituents of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 34 publications
(37 reference statements)
1
19
0
Order By: Relevance
“…Because high gliding resistance causes more adhesions (Zhao et al, 2001a, 2001b) we tried to decrease the gliding resistance for extrasynovial tendon autografts. We found that tendon surface modification with chemically modified hyaluronic acid could improve grafted extrasynovial tendon gliding ability in vitro and in vivo (Momose et al, 2002; Sun et al, 2004; Taguchi et al, 2008; Tanaka et al, 2006, 2007; Yang et al, 2004; Zhao et al, 2006). In addition, we recently reported that this tendon surface treatment, combined with gelatin, significantly improved gliding ability of lyophilized tendon as well (Ikeda et al, 2010).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Because high gliding resistance causes more adhesions (Zhao et al, 2001a, 2001b) we tried to decrease the gliding resistance for extrasynovial tendon autografts. We found that tendon surface modification with chemically modified hyaluronic acid could improve grafted extrasynovial tendon gliding ability in vitro and in vivo (Momose et al, 2002; Sun et al, 2004; Taguchi et al, 2008; Tanaka et al, 2006, 2007; Yang et al, 2004; Zhao et al, 2006). In addition, we recently reported that this tendon surface treatment, combined with gelatin, significantly improved gliding ability of lyophilized tendon as well (Ikeda et al, 2010).…”
Section: Discussionmentioning
confidence: 95%
“…However, the gliding ability of intrasynovial tendons prepared by lyophilization, a common method of preservation, is significantly decreased (Ikeda et al, 2010). To increase the tendon gliding ability, surface modification with carbodiimide derivatized hyaluronic acid (cd-HA) has been well studied (Ikeda et al, 2010; Momose et al, 2002; Sun et al, 2004; Taguchi et al, 2008; Tanaka et al, 2006; Yang et al, 2004). This surface modification indeed has been recently reported to mitigate this adverse effect, leading to decreased postoperative adhesions (Zhao et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…33 We found that the increase in gliding resistance was reversed through surface modification with cd-HA-gelatin. The efficacy of this modification has been reported in both in vitro 33,48 and in vivo 39,49 models. Karabekmez and Zhao reported that surface modification with cd-HA decreased the adhesion formation without altering the cellularity in either the autologous extrasynovial tendon or the intrasynovial allograft in an in vivo canine model.…”
Section: Discussionmentioning
confidence: 99%
“…Second, we did not determine if wear was enhanced following a reduction in lubricin content. Our previous studies showed that flexor tendons could maintain an intact surface during up to 1000 cycles of repetitive motion 27,41 . This suggests that lubricin, a component of the flexor tendon surface, resists wear.…”
Section: Discussionmentioning
confidence: 99%